Extreme Meteorological Events in a Coastal Lagoon Ecosystem: The Ria de Aveiro Lagoon (Portugal) Case Study - José Fortes Lopes; Carina Lurdes Lopes; João Miguel Dias (Journal of Marine Science and Engineering, 2021)
Extreme weather events (EWEs) represent meteorological hazards for coastal lagoon hydrodynamics, of which intensity and frequency are increasing over the last decades as a consequence of climate changes. The imbalances they generated should affect primarily vulnerable low-lying areas while potentially disturbing the physical balances (salt and water temperature) and, therefore, the ecosystem equilibrium. This study arises from the need to assess the impact of EWEs on the Ria de Aveiro, a lagoon situated in the Portuguese coastal area. Furthermore, it was considered that those events occur under the frame of a future sea-level rise, as predicted by several climate change scenarios. Two EWEs scenarios, a dry and an extremely wet early summer reflecting past situations and likely to occur in the future, were considered to assess the departure from the system baseline functioning. It was used as a biogeochemistry model that simulates the hydrodynamics, as well as the baseline physical and biogeochemistry state variables. The dry summer scenario, corresponding to a significant reduction in the river’s inflow, evidences a shift of the system to a situation under oceanic dominance characterized by colder and saltier water (~18 °C; 34 PSU) than the baseline while lowering the concentration of the nutrients and reducing the phytoplankton population to a low-level limit. Under a wet summer scenario, the lagoon shifted to a brackish and warmer situation (~21 °C, <15 PSU) in a time scale of some tidal periods, driven by the combining effect of the tidal transport and the river’s inflow. Phytoplankton patterns respond to variability on local and short-term scales that reflect physical conditions within the lagoon, inducing nutrient-supported growth. Overall, the results indicate that EWEs generate local and transient changes in physical conditions (namely salinity and water temperature) in response to the characteristic variability of the lagoon’s hydrodynamics associated with a tidal-dominated system. Therefore, in addition to the potential impact of changing physical conditions on the ecosystem, saline intrusion along the lagoon or the transfer of brackish water to the mouth of the system are the main consequences of EWEs, while the main biogeochemistry changes tend to remain moderate.